Scientific Opinion on Flavouring Group Evaluation 13 Revision 3 (FGE.13Rev3): furfuryl and furan derivatives with and without additional side‐chain substituents and heteroatoms from chemical group 14. (3rd February 2021) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gundert‐Remy, Ursula; Gürtler, Rainer; Husøy, Trine; Manco, Melania; et al.
Abstract: The Panel on Food additives and Flavourings of the EFSA was requested to update Flavouring Group Evaluation 13 using the Procedure as outlined in Commission Regulation (EC) No 1565/2000, to include an evaluation of the flavouring substances 2‐ethyl‐5‐methylfuran [FL‐no: 13.125] and 2‐octylfuran [FL‐no: 13.162]. FGE.13 revision 3 (FGE.13Rev3) deals with 26 flavourings substances of which 24 have been already evaluated to be of no safety concern. For [FL‐no: 13.125] and [FL‐no: 13.162], a concern for genotoxicity was raised in FGE.13Rev1. This concern could be ruled out based on new genotoxicity data on supporting substances in FGE.67Rev3. Subsequently, [FL‐no: 13.125 and 13.162] were evaluated, through a stepwise approach that integrates intake from current uses, toxicological threshold of concern (TTC), and available data on metabolism and toxicity, along the B‐side of the Procedure, making use of a BMDL of 8.51 mg/kg body weight (bw) per day. The Panel derived this BMDL from an oral subchronic toxicity study with the supporting substance 2‐pentylfuran [FL‐no: 13.059]. Using this BMDL, for [FL‐no: 13.125 and 13.162], adequate margins of safety were calculated based on the MSDI approach. The Panel concluded that the 26 candidate substances in FGE.13Rev3 do not give rise to safety concerns at their levels of dietary intake, when estimated on the basis of the MSDI approach. Adequate specifications for the materials of commerce have been provided for all 26 substances. Data on uses and use levels are needed for [FL‐no: 13.130]. For 21 flavouring substances [FL‐no: 13.011, 13.102, 13.108, 13.113, 13.114, 13.122, 13.125, 13.127, 13.129, 13.132, 13.133, 13.135, 13.136, 13.139, 13.141, 13.143, 13.146, 13.149, 13.162, 13.178 and 13.185], the mTAMDI intake estimates are above the TTC for their structural class and more reliable data on uses and use levels are required to finalise their evaluation.